MECHANICAL WORK AND AUTOMATICITY OF THE HEART (Лучшие интеллектуальные исследования, 2025)
Abstract: The human heart operates as a remarkable biological pump, seamlessly integrating mechanical and electrical functions to maintain systemic circulation. This dual role is essential for sustaining life, as mechanical work ensures effective blood propulsion while automaticity enables the intrinsic generation and regulation of cardiac rhythm. Understanding how these processes interact at cellular and molecular levels is fundamental to advancing treatments for cardiovascular diseases. Recent research highlights the complexity of electro-mechanical coupling, particularly the pivotal role of calcium signaling pathways in orchestrating contraction and electrical activity. Alterations in these pathways can precipitate cardiac dysfunctions such as arrhythmias and heart failure, underscoring the significance of targeted investigations into the heart’s automaticity and mechanical performance. Insights gained from studying the heart’s dynamic physiological responses and mechanical demands contribute to improved therapeutic strategies and bioengineering applications aimed at supporting cardiac health in both normal and pathological states (Bannerot et al.) (Lang et al.).